Efecto de Tres Crioprotectores en la Criopreservación de Espermatozoides Epididimarios de Alpaca - Terreros C., Marino (2015)
The study aimed to evaluate the effect of three cryoprotectants: Dimetil Sulfoxide (DMSO), Ethylene glycol (EG) and Glycerol (GL) on the cryopreservation of epididymal alpaca sperm. Testicles of alpacas older than 3 years were used. The epididymides were separated and the tails were dissected. The spermatozoa were recovered with fraction A of the extender (cow skim milk, egg yolk and fructose), selecting samples with sperm motility equal or higher than 50% (n=18, motility = 69%, sperm membrane functional integrity = 48%). The fraction A with the sperm was refrigerated (cooling rate of 1 ºC/5 min) until 5 ºC. The fraction was divided in three and added the same volume of fraction B with the cryoprotectant (DMSO: 7%, 0.9M; EG: 7%, 0.9M; GL: 7%, 1.2M). Then, 0.5 ml straws were filled with the final dilution and frozen in liquid nitrogen. After 7 days of storage, the post-thaw motilities were 31, 8 and 24% and percentages of sperm membrane functional integrity were 28, 17 and 26% for DMSO, EG and GL respectively. An in vitro fertilization trial was conducted with thawed sperm from groups DMSO and GL, where the cleavage rate at 72 h post-fertilization was 47 and 27% respectively and without statistical difference. The results suggest that dimetil sulfoxide and glycerol are more efficient cryoprotective agents in comparison to the ethylene glycol.